Life Of Problem Women (WTS) In Bandar New Village (Case Study Of Three Prostitute Women At The Florida Bandar Baru Hotel) - Desi Yulianti (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2021)
This paper wants to know the phenomenon of the life of Women Tuna Susila (WTS) at the florida Hotel in Bandar Baru village. Everyday prostitutes who sell themselves to meet the needs, improve the economic conditions and patterns of interaction created between fellow prostitutes and the surrounding community. Knowing their true conditions, the difficulties of being a prostitute, and the localization places under the bungalows and hotels in Bandar Baru Village. Although the government and local communities do not refuse and do not support prostitution activities. Therefore researchers interested in researching the lives of prostitutes. The technique of selecting information using snowballs technique is a key information statement that is the most important informant in developing and finding for key informants and additional informants key informant is a trader who has been fifteen years of trading around the hotel and bungalows whose customers are mostly prostitutes, who is experienced and knows a lot about the life of prostitutes. This research uses explorative type of research because this research tries to dig up information or problems that are relatively new, and uses data collection techniques through putaka study, observation and interview. Data obtained in the field and then explored with a qualitative approach, until finally draw conclusions from the results of these studies. The results of the study,life.